PERAN ORGANISASI SOSIAL DALAM KESEJAHTERAAN SOSIAL DI KOTA KUPANG - Jayaputra, Achmadi (Puslitbangkesos, 2006)
(Social Organization's Role on Social Welfare in Kupang City) - Social organization is a place for community and society to improve the member's welfare. This study is about social organization in Kupang city to understand organization social role in social welfare service and identify factors which influence the organization. The problem is whether social organization can hold activities about social welfare or not. Data collecting was done through interview and limited discussion was done with some respondents consisting of society and social organization's staff. The result of the study shows that there are some characteristic the local social organization considering social welfare activities based on the purpose. While other local social organization didn't do it because they didn't get guidance from social institutions.